Oral pyogenic granuloma with calcification - Akancha Singh Gautam; Sneh Mandal; V. C. Divya (Wolters Kluwer Medknow Publications, 2024)
Rationale: Pyogenic granuloma (PG) is a commonly observed reactive soft-tissue lesion, often arising due to prolonged mild irritation or hormonal fluctuations in the oral cavity. Clinically, PG presents as a lesion with a smooth or lobulated appearance, which can be either sessile or pedunculated, and typically exhibits an hemorrhagic tendency. Very few cases of calcification in a PG have been reported in the past as these rarely exhibit ossification when viewed under a microscope. Patient Concerns: The following report is a case of a PG, that presented as a growth with occasional pain in the right upper back region of a 54 year old female. The patient reported no other concerns. Diagnosis: A provisional diagnosis of PG was given following thorough clinical and radiographic investigations. This was confirmed by a histopathological examination following an excisional biopsy. Intervention: The patient was treated with surgical excision as a part of the excisional biopsy of the lesion. Follow-up for the patient was done after 6 months, and there were no signs or indications of recurrence. Outcomes: The histopathological examination revealed regions of calcification, which are uncommon in PG, in addition to the characteristic hallmarks of proliferating endothelial cells, blood vessels, and inflammatory cells.